Assessing the Environmental Impacts of Urban Mixed Land-Use on Residential Livability: A Case Study of Hyderabad - Fatima, Mutiba; Mushtaque, Daniyal (Journal of Environmental Science and Engineering Technology, 2025)
Background; Livability is increasingly recognised as a central component of sustainable urban development, and in rapidly commercialising cities, mixed-use corridors play a critical role in shaping daily experiences. Objective; The current research examined environmental quality conditions along four mixed-use commercial corridors to determine how spatial variations in key urban environmental stressors including noise exposure, sanitation, greenery availability and environmental infrastructure reflect the effectiveness of urban environmental management practices in dense mixed-use settings. Methods; The current study adopted a quantitative, cross-sectional survey design. Data were collected using a structured questionnaire administered to residents and routine users located along each commercial corridor. A purposive sampling method was employed to select 96 participants who had resided in the area for at least one year. The sample was proportionally distributed across the four study corridors. Seven livability indicators were assessed, including public health, environmental quality, mobility, public space, social equity, economic opportunities, and basic utilities. Furthermore, descriptive statistics and comparative analyses were conducted to examine differences across the four locations. Results; The findings indicate that livability varies considerably across the commercial corridors. Most indicators received the highest scores on Dr. Salahuddin Road (overall mean = 3.28), suggesting more favourable perceptions of cleanliness, utility provision, clinical accessibility, mobility, and economic potential. In contrast, Wadhu Wah Road demonstrated the lowest overall livability (overall mean = 2.80), which was associated with limited greenery, inadequate pedestrian infrastructure, elevated noise levels, and suboptimal waste management. Moreover, the rating of public utilities and social interaction remained relatively positive across all areas (mean ≥ 3.05), whereas walkability (mean range: 2.70–2.95) and the availability of public spaces (mean range: 3.09–3.28) consistently emerged as weaknesses. Conclusion; The current study reveals that a well-planned pattern of commercial development can substantially improve living conditions and reduce congestion, environmental discomfort, and risks associated with pedestrian movement.